BioRaCe NiTi system: Biologically desirable apical sizes - safely and efficiently - Debelian Gilberto (Serbian Medical Society - Dental Section, Belgrade, 2011)
The main goal of endodontic treatment is an effective cleaning and shaping of the root canal in order to eliminate bacteria from the canal system and prevent the occurrence of apical periodontitis. Adequate choice of instruments and preparation techniques significantly reduce the number of bacteria in the canal system prior to obturation. Studies have confirmed that canals instrumented to acceptable apical diameters provide significantly lower number of bacteria even without the use of irrigation. Application of rotary instruments, such as BioRaCe, provides biologi- cally appropriate diameter in the apical portion of the canal and thus a lower number of residual bacteria to ensure safe and effective obturation.